Designing language activities using Second Life - Abd. Hamid, Mohd Azrul Azlen; Abdullah, Aishah@Adeline Low Hui Lin; Mat Daud, Nuraihan (IIUM Press, 2012)
Second life (SL) promises the possibility for the development of useful and meaningful learning activities in various educational environments. SL should be viewed as an adjunct to classroom teaching and also other online e-learning activities and applications. It has the potential to enrich and enhance educational activities. SL serves as a platform for collaborative learning and authentic exchanges. This paper discusses the possible applications of SL including for learning and teaching.